Interiority: At the Threshold - Atmodiwirjo, Paramita; Yatmo, Yandi Andri (Interiority, 2019)
Being at the threshold offers an ambiguous spatial experience. The idea of threshold is relevant to the discourse of interiority, as it expands our understanding of the opposing condition of inside-outside, or interior-exterior, which have become the recurring themes in many discussions on interiority. This issue of Interiority attempts to address what actually occurs at the threshold – the occupation and the experience of the threshold. The contributors in this issue address the emergence of spatial ideas that define the new relationship between inside and outside, between interior and architecture.